Comments on the criminal protection of the capital market in Poland - Płońska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The development of the capital market in Poland in recent years is also associated with various types of prohibited acts that threaten both individual and general public legal interests. The importance of criminal protection of the capital market is essential when other means of legal responses are not effective. The author indicates the protective function of criminal law as the most significant. Then the author presents an overview of the Polish capital market and criminal liability for the majority of capital market offences.
Keywords: przestępstwa "białych kołnierzyków"; przestępstwa umysłowe; rynek kapitałowy; odpowiedzialność karna; przestępstwa giełdowe